1995
DOI: 10.1002/gps.930100105
|View full text |Cite
|
Sign up to set email alerts
|

The impact of home assessment on depression in the elderly: A clinical trial

Abstract: Many consider home assessment important to the evaluation and management of elderly patients with mental disorders but no controlled studies of the impact of this activity have been reported. Thus, we conducted a clinical trial to determine if home assessment was more effective than clinic assessment in eliciting useful clinical information and in reducing depression, anxiety, functional disability and social isolation among elderly depressed patients referred to an outpatient clinic. Thirty‐two patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In many of the included trials, subjective and/or objective social isolation was one of several outcomes (with no clearly specified primary outcome), and for some trials, strategies to reduce social isolation were part of an often much broader service improvement approach (e.g. [70,74,76,89]). Just six trials [43,72,73,75,86,87] had a measure of social isolation as the clearly stated primary outcome.…”
Section: Overall Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many of the included trials, subjective and/or objective social isolation was one of several outcomes (with no clearly specified primary outcome), and for some trials, strategies to reduce social isolation were part of an often much broader service improvement approach (e.g. [70,74,76,89]). Just six trials [43,72,73,75,86,87] had a measure of social isolation as the clearly stated primary outcome.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Of the six trials that compared an active treatment group with a control group [67-69, 71, 73, 76], findings of four trials suggested superior outcomes for their intervention groups over their control groups on objective social isolation measures: a psychoeducation programme for adults with schizophrenia [67], a social network intervention for people diagnosed with schizophrenia spectrum disorders [73], a preventive senior centre group for seniors with mild depression [69], and Social Cognition and Interaction Training (SCIT) for patients with various diagnoses [68]. One trial involving social education for people with schizophrenia and one trial involving home assessment teams for people with mood disorders did not lead to any improvements in objective social isolation [71,76].…”
Section: Interventions To Reduce Objective Social Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the arguments favouring home or hospital assessment are essentially impressionistic. A single randomised, but small, study has compared the quality of assessment and outcome of elderly depressed referrals seen at home or in hospital and found no significant difference (Cole et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all of the evidence has favoured home assessment. One trial of 32 elderly patients with depression who were cognitively intact failed to demonstrate an improvement in assessment or outcomes when comparing home assessments with clinic assessments (Cole 1995).…”
mentioning
confidence: 99%